HARMONISASI NILAI-NILAI PANCASILA DALAM PEMBANGUNAN HUKUM YANG BERKEADILAN DITINJAU DARI PERSPEKTIF HUKUM DAN HAK ASASI MANUSIA - Aprita, Serlika; Mutiara Paramitha; Fira Rahmawati (The Juris, 2022)
Harmonization of law is an important part of Indonesian law. the characteristics of justice based on Pancasila are values in the form of principles of justice or principles based on the One Godhead. Upholding justice based on justice from God, justice, and humanity as principles of justice that upholds to create an atmosphere that supports justice for Indonesian citizens. Pancasila is used in the formation of law or becomes the main milestone in forming laws and regulations that are in accordance with the spirit of the Indonesian nation which humanizes just and civilized humans and is socially just for all Indonesian people.